A study of the transformation of Michael Ondaatje's The English Patient from novel to film - Shereen Shabnam
The overall aim of this study is to inverstiage the transformation of Michael Ondaatje's novel The English Patient into a film directed by Anthony Minghella adn to analyze the differences in the two genres. Both versions of The English Patient have been studied in conjunction with detailed appendices of the sequence of scene s which were created to serve as sources of data for the research. Detailed attention is given to the Islamically relevant elements in each work. Theories of Alistair Fowler, George Bluestone, Christian Merz and Brian McFarlane are used to analyze the possible reasons behind the significant changes in the Film version of The English patient and its possible effect, particularly to the Muslim audience. The study concludes that genre transformation helps in unraveling different layers of subjects and themes, giving a broader view of the original work. The inclusion of Islamically-relevant elements is studiedd at three levels; simple, suggestive and complex elements. The study shows that complex elements are more provocative or negatively stereotyped and therefore may evoke reactions from the Muslim audience. The research is important to literature students and people specializing in literary studies. The study also opens possibilities of research in transformations of novels to films according to their locations, themes and origins. Additionally, the possibility of further research in areas related to genre transformation is recommended not only from novel to film, but also other types of transformations such as sonnets to songs, plays to films, etc.